The Prevalence and Incidence of Latent Tuberculosis Infection and Its Associated Factors among Village Doctors in China. - Guangxue He; Yuan Li; Fei Zhao; Lixia Wang; Shiming Cheng; Hui Guo; John D Klena; Haiying Fan; Fangfang Gao; Fei Gao; Guoxin Han; Liping Ren; et al. (PLoS ONE, 2015)
Background China is a high tuberculosis (TB) burden country. More than half of acute TB cases first seek medical care in village doctors' clinics or community health centers. Despite being responsible for patient referral and management, village doctors are not systematically evaluated for TB infection or disease. We assessed prevalence and incidence of latent TB infection (LTBI) among village doctors in China. Methods and findings A longitudinal study was conducted in Inner Mongolia Autonomous Region. We administered a questionnaire on demographics and risk factors for TB exposure and disease; Tuberculin skin testing (TST) and QuantiFERON-TB Gold in-tube assay (QFT-GIT) was conducted at baseline and repeated 12 months later. We used a logistic regression model to calculate adjusted odds ratios (ORs) for risk factors for TST and QFT-GIT prevalence and incidence. At the time of follow up, 19.5% of the 880 participating village doctors had a positive TST and 46.0% had a positive QFT-GIT result. Factors associated with TST prevalence included having a BCG scar (OR = 1.45, 95%CI 1.03-2.04) and smoking (OR = 1.69, 95%CI 1.17-2.44). Risk factors associated with QFT-GIT prevalence included being male (OR = 2.17, 95%CI 1.63-2.89), below college education (OR=1.42, 95%CI 1.01-1.97), and working for ≥25 years as a village doctor (OR = 1.64, 95%CI 1.12-2.39). The annual incidence of LTBI was 11.4% by TST and 19.1% by QFT-GIT. QFT-GIT conversion was associated with spending 15 minutes or more per patient on average (OR = 2.62, 95%CI 1.39-4.97) and having BCG scar (OR = 0.53, 95%CI 0.28-1.00). Conclusions Prevalence and incidence of LTBI among Chinese village doctors is high. TB infection control measures should be strengthened among village doctors and at village healthcare settings.